The Contemporary Attitudes in the Spatial Formation for the Residential Urban Fabric and Applied Solutions in Lattakia City - Alshaikh, Ramzi (Latakia University Journal -Engineering Sciences Series, 2019)
The Study focuses on the contemporary planning applications in shaping the urban structure of the residential areas in general and the spatial formation in particular, according to a schematic structure that depends on classification of these spaces by kind, function of these special formation and their distinguished characteristics. The study focuses on the gradual scales of the formed spaces within the urban residential structure according to their functions, starting with the external courtyards surrounded by residential buildings whose construction in open space differs from the one in closed space, according to the predominant climatic conditions, then we move to the spaces of motorcar streets and pedestrians roads that have the dynamic and vitality characteristic by the multiplicity of uses, the functions, and the changes of its design structure. Spaces surrounding the public and service buildings form some special distinctive structural points especially when they complement each other with the surrounding buildings in architecture and volume. The formation of aesthetic-visual image in the urban spaces and the visual recognition mechanism divides the urban spaces into three principal types and discusses the relationship between shapes, volumes and colors of the building that form the space and visual sensation with the homogeneity and extension of space. Then the research studies various samples of the urban residential structure of Lattakia city and the spatial formation by performing general classifications of the urban spaces forming this structure according to the type and function of each. Then, we conclude the advantages and disadvantages of the schematic solution and understand the reasons of the negative aspect to be avoided in future. يلقي البحث الضوء على التطبيقات التخطيطية المعاصرة في تشكيل النسيج العمراني للمناطق السكنية بشكل عام والتكوين الفراغي لهذا النسيج بشكل خاص، وذلك وفقاً لهيكلية تخطيطية تعتمد على تصنيف هذه الفراغات استناداً إلى نوع ووظيفة كل فراغ وإبراز شخصيته المتميزة. يركز البحث على دراسة التدرج المقياسي للفراغات المتشكلة ضمن النسيج العمراني السكني بحسب وظائفها والتي تبدأ من الأفنية الخارجية المحاطة بالأبنية السكنية التي يختلف تكوينها من فراغ مفتوح إلى فراغ مغلق، وفقاً للظروف المناخية السائدة مروراً بفراغات شوارع السيارات وطرق المشاة التي تمتلك ميزة الديناميكية والحيوية من خلال تعددية وظائفها واستعمالاتها وتغيير بنيتها التصميمية، وتشكل الفراغات المحيطة بالأبنية العامة والخدمية نقاطاً تكوينية مميزة خاصة عندما تتكامل معمارياً وحجمياً مع كتل الأبنية المجاورة لها. إن تشكيل الصورة الجمالية – البصرية للفراغات في النسيج العمراني السكني وآلية الإدراك البصري باحتواء الفراغ مقسماً الفراغات العمرانية إلى ثلاثة أنواع رئيسية ومن ثم مناقشة العلاقة بين أشكال وأحجام وألوان المباني المشكلة للفراغ والإحساس البصري بتجانس واتساع الفراغ. ينتقل البحث إلى دراسة عينات مختلفة من النسيج العمراني السكني لمدينة اللاذقية والتكوين الفراغي له وذلك من خلال إجراء تصنيف عام للفراغات العمرانية المشكلة لهذا التكوين وفقاً لنوع وظيفة كل منها، ومن ثم استنتاج سلبيات وإيجابيات الحل التخطيطي المعتمد ومحاولة الوقوف على الأسباب التي أدت إلى وجود الجوانب السلبية ليتم تفاديها في الحلول المستقبلية.